Quality factors that affect the productivity and competitiveness of micros, small and medium enterprises of the metalworking sector (2019)
This article defines concepts that are associated to quality, productivity and competitiveness, and proposes a standardized measuring way of the productivity within processes. It explains the factors and guidelines of quality that permit an organization to evolve through different phases of quality, in order to increase productivity and competitiveness facing the domestic and international markets. It establishes tools, factors and guidelines of quality applied by micro, small and medium enterprises of the metalworking sector in Pereira and Dosquebradas, and the quality phase in which they are currently. It explores the voluntary and regulatory conditions that the market and the national government require to products and companies of the industrial sector under study.